Implementation of decarbonisation actions in general practice: a systematic review and narrative synthesis - Jeremy Dale; Helen Atherton; Ana Raquel Nunes; Abi Eccles; Rachel Spencer; Helen Twohig; Florence Karaba; Olivia Geddes; Frederik Dahlmann; Michael Gregg; Abi Bickerton (BMJ Open)
Objectives To summarise and synthesise existing literature on the implementation of decarbonisation actions in general practice, to outline the actions being implemented, factors influencing decarbonisation, identify evidence gaps and questions for future research.Design A systematic review and narrative synthesis.Data sources MEDLINE, Embase, CINAHL, Web of Science and ProQuest (grey literature) were searched for literature published up to 29 March 2024.Eligibility criteria for selecting studies Studies of any design investigating the implementation of decarbonisation actions in general practice.Data extraction and synthesis Two reviewers extracted data and conducted quality assessments using a mixed methods appraisal tool. Narrative synthesis was used to analyse findings.Results Fifteen studies were included. Studies were primarily from the UK (n=5), followed by Australia (n=3), USA (n=2), Germany (n=2) and one each from France, Switzerland and Israel. Study designs were qualitative (n=7), quantitative (n=7) and one mixed methods. Participants included healthcare staff (n=7), patients (n=5), health stakeholders (n=2) and the general public (n=1). There was evidence of general practices adopting decarbonisation actions such as resource reuse, improved waste management, energy-efficient systems and preventive care to reduce overmedication, with strong leadership and institutional support being crucial for their success. However, barriers such as high costs, resource constraints and limited awareness among clinicians and patients highlighted the need for enhanced communication, education and the structured promotion of initiatives to improve patient and community engagement.Conclusions There is limited evidence on the implementation of decarbonisation actions in general practice. A range of factors may impact on the extent to which implementation occurs. Addressing these will be crucial for effectively promoting and scaling decarbonisation actions in general practice. Future research should focus on understanding the role of institutional context, evaluating the real-world impact of interventions on greenhouse gas emissions and exploring patient and community involvement.PROSPERO registration number CRD42023470889.